KAJIAN KRITIK SANAD DAN MATAN HADIS TENTANG PERINTAH SHALAT TERHADAP ANAK - Muhsin, Muhsin (Pusat Studi Gender dan Anak, IAIN Palu, 2018)
Prayer is one of the pillars of Islam, therefore the importance of the command of the Prayer from the beginning applied by the Prophet has its own wisdom. In this case, this writer wants to study the hadith of the Prophet Muhammad about the command of prayer. Using the Takhrij Hadith method, the hadith can be known whether he belongs to the Shohih Hadith or the Dhaif Hadith. This is very important because the hadith of the Prophet Muhammad is the second source of law in Islam, of course this is very influential in Islamic law. Therefore this paper aims to clarify the status of a hadith which explains the command of prayer for children. ` Takhrij hadith the author will use the dictionary Takhrij hadith namely Kitab Mu'jam al-Mufahraz. After each of the narrators will be examined one by one, so that the hadith to be studied can be traced whether this hadith is dhaif or Shahih If the results are shohih, then it will give confidence that educating children from a small age, especially prayer, is the guidance of the true Prophet. If the hadith is of value, then the hadith can still be used to motivate children about the prayer service. The reason for writing this article is because there are so many who doubt the credibility of a hadith that causing hadith to be one of the